(untitled) (Baltic Journal of Sport and Health Sciences, 2021)
Background. Return to participation in sport is an important outcome when evaluating the success of anterior cruciate ligament (ACL) reconstruction surgery. A review by Arden et al. (2014) demonstrates that just because an athlete has surgery, it does not automatically mean that they will return to sport. So, the purpose of this study was to assess if patients could return to their pre-injury activity level 8 months after ACLR. Methods. Patients completed IKDC-2000, ACL-RSI questionnaires, underwent FMS, YBT, HOP test sets and drop jump tests, which were evaluated with the LESS. ACL laxity was measured by using a GNRB® device. Participants were 81 patients. They were divided into two groups based on single leg HOP test results. The first group included 30 persons who all had their four single leg HOP test scores above 90%. The second group consisted of 51 persons for whom at least one of the single leg HOP tests scored lower than 90%. Results. IKDC and HOP test results in the first group scored higher than in the second group. Psychological confidence was higher in the first group, who had better HOP test results. For the first group, FMS and LESS results were better than those for the second group. Moderate positive correlation was found between LESS scores and laxity results, FMS, three HOP sub-tests. IKDC had the biggest number of correlations with other tests. Results showed negative and weak correlation with laxity results using 134 N power, as well as positive and moderate correlation with HOP sub-tests, FMS, ACL-RSI. Single HOP for distance, triple HOP for distance, crossover HOP for distance and LESS increased the odds of achieving RTS criteria. No other factors were found to be associated with the accomplishment of reaching RTS criteria after ACLR. Conclusions. The main factor which can help decide if a person can return to their pre-injury level of physical activity are the single leg HOP test and LESS. The use of single leg HOP tests and LESS along with psychological and self-reported evaluations is the best test combination for assessment 8 months after ACLR. Keywords: ACL reconstruction, function tests, return to play, jump tests, psychological readiness.